THE CLINICAL CASE OF SURGICAL TREATMENT PARIETAL AND POSTERIOR FOSSA EPIDURAL HEMATOMA - Bogdan І.С.; Ratcyn І.М.; Bondarchuk Б.В.; Cysnetsky В.В.; Kovalishin О.А. (Actual Problems of Medicine and Pharmacy, 2021)
A case of surgical treatment of the patient with parietal and occipital fossa epidural hematoma is presented. X-ray examination didn’t reveal a fracture of paretal os. MRI diagnosed parietal and posterior fossa epidural hematoma. During the craniectomy realived fracrure of the parietal os, epidural hematoma removed. The souse of the bleeding was veins-perforates of the skill. A dynamic MRI found a positive outcome. The parient withdraw on the 10 day after operation.